Designing Tour Guide English Materials for Tourist Village Community of 3T Regions in Buru Island - Hajar, Ibnu; Atmowardoyo, Haryanto; Taufik, Taufik; Rusdi, M.; Bugis, Riki; Tahir, Saidna Zulfikar Bin (Journal of Ecohumanism, 2024)
Tourist villages are destinations visited by both domestic and international travelers, necessitating human resources proficient in English to engage with international guests. Accordingly, this study aims to: 1) Identify the needs of the tourist village community for tour guide English materials, 2) Design English for tour guide materials for the tourist village community in 3T regions, and 3) Evaluate the effectiveness of the English for tour guide materials implemented in the tourist village. This research employs the research and development method to investigate the community's needs for tour guide English materials. A total of 350 respondents were selected from six tourist villages located in four districts on Buru Island, classified as 3T areas. Based on the results of the questionnaires distributed, an English pocketbook for beginner tour guides was designed. This textbook was then implemented in a small-scale trial involving 15 participants to evaluate its effectiveness and gather feedback for improvement. The findings reveal that the tourist village community requires English materials focused on basic greetings, directions, and culinary-related vocabulary to effectively serve foreign tourists. Ultimately, this study underscores the significance of designed English materials in empowering local communities in 3T regions to participate in the tourism industry.